Asymmetric exchange rate pass-through to inflation in Vietnam: Evidence from a nonlinear ARDL approach - Nguyet, Ngo Anh (Edelweiss Applied Science and Technology, 2026)
This paper investigates asymmetric exchange rate pass-through (ERPT) to consumer price inflation in Vietnam over the period January 2005 to December 2023. Employing the nonlinear autoregressive distributed lag (NARDL) framework of Shin et al. [1], we decompose exchange rate changes into positive (VND depreciation) and negative (VND appreciation) partial sums and estimate their differential effects on Vietnam’s Consumer Price Index. The F-bounds statistic (F = 3.84) exceeds the 10 percent upper critical bound, confirming a level relationship. The oil price channel is the statistically dominant long-run driver: a ten-percent increase in Dubai crude is associated with approximately 3.2 percent higher CPI. The speed-of-adjustment coefficient is individually insignificant, consistent with Vietnam’s managed exchange rate regime; we therefore rely on cumulative dynamic multipliers as the primary ERPT measure. These reveal that VND depreciation generates a larger inflationary impulse (converging at ≈+0.6 log-CPI units over 24 months) than appreciation generates a deflationary offset (≈−0.4), evidencing short-run asymmetry. The CUSUM test confirms structural stability throughout 2005–2023. Rolling-window estimates reveal elevated ERPT intensity during the 2022–2023 Federal Reserve tightening cycle. These findings offer policy insights for the State Bank of Vietnam in calibrating asymmetric exchange rate interventions to anchor inflation expectations.